Analysis of Factors Influencing Women’s Decision to Work as Traders in Badung Market - Indira Mayhesa Tamba; Ida Ayu Nyoman Saskara (International Forum of Researchers and Lecturers, 2025)
Badung Market, as one of the largest traditional markets in Denpasar City, serves as a central hub of economic activity and sustains the livelihood of a substantial number of women traders. The presence of women in this sector is not only a reflection of their economic role but also of their contribution to household welfare and community development. This study aims to analyze the influence of education, income, dependents, and age on women’s decisions to work as traders in Pasar Badung. Employing a quantitative approach with an associative design, the research involved 88 respondents selected through purposive sampling from a total population of 768 female traders. Data collection methods included questionnaires, direct observation, and interviews, while data analysis utilized multiple linear regression preceded by validity, reliability, and classical assumption tests to ensure robustness. The results indicate that, simultaneously, all independent variables significantly affect women’s decision to engage in trading activities. Partially, education, dependents, and age show a significant positive effect, suggesting that higher educational attainment, greater family responsibilities, and maturity increase women’s participation in trading. In contrast, husband’s income exerts a significant negative effect, implying that higher spousal earnings reduce the economic pressure for women to seek income through market trading. These findings highlight that economic necessity, household responsibilities, and social roles remain the primary motivators for women’s active involvement in traditional market activities. The implications of this study are relevant for policymakers and local governments, particularly in designing targeted empowerment programs, skills training, and economic support mechanisms to enhance women’s entrepreneurial capacity in traditional markets. Strengthening women’s roles in this sector is crucial not only for family welfare but also for broader community resilience and local economic growth.